2017
DOI: 10.7547/15-167
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infection with Pseudomonas aeruginosa in Diabetic Foot Infections

Abstract: This retrospective study provides some information on risk factors for infection with this difficult pathogen in patients with DFI. We need prospective studies in various parts of the world to better define this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 19 publications
1
25
1
4
Order By: Relevance
“…The IDSA recommends empirically covering PsA in cases of high local prevalence (undefined in the guidance), warm climate, and frequent exposure of the feet to water [ 1 ]. Other reported risk factors include a history of amputation, wound dressings, and chronic kidney disease [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IDSA recommends empirically covering PsA in cases of high local prevalence (undefined in the guidance), warm climate, and frequent exposure of the feet to water [ 1 ]. Other reported risk factors include a history of amputation, wound dressings, and chronic kidney disease [ 5 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, results were variable. Studies have found that Staphylococcus aureus is the main causative pathogen [16][17][18], but others have reported a predominance of Gram-negative aerobes [19,20]. These discrepancies could be related to various factors, such as the presence of different causative organisms at different times, geographical variations and ecologies, socio-economic conditions, hygiene, accessibility to effective health care services, the type and the severity of the infections, or depth of the wound and sampling technique [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It has been suggested that high levels of moisture in the wound and a history of using active wound dressings facilitate the growth of P aeruginosa . 24 Additionally, wet dressings, excessive exudate, preference for autolytic debridement, particularly in the presence of necrosis instead of surgical debridement, or in cases where surgical debridement cannot be performed immediately, may play a role in this predisposition. It should be mentioned that it is also important to leave infections of the finger spaces as wet.…”
Section: Discussionmentioning
confidence: 99%